Electromobility: Safety or a Threat to Poland’s Transport? - Katarzyna Głodowska (Polish Political Science Yearbook)
The trend following the purchase of electric-powered vehicles is currently the biggest challenge of the Polish automotive industry. Increasing restrictions and looming deadlines for selling electric-only cars contribute to their increasing purchase numbers. It is known that electric vehicles require a stable charging infrastructure. From 2020 to 2022, infrastructure development is significant in Poland, but is it sufficient? Is this the main drawback of owning an electric vehicle? More and more users are charging their cars locally at their places of residence, but not everyone has this option. This raises the question of whether it is safe to own an electric vehicle. Is it possible to cover the route from point A to point B without much trouble? Awareness of the need to stop longer to charge an electric vehicle is not a problem among the Polish public; a bigger and more significant issue is the number of publicly available charging points. Therefore, these topics will be analyzed more extensively in this article; the possibilities of alternative charging and energy harvesting methods will be presented, as the growing interest in electric-powered vehicles and the indicated questions regarding the development of charging infrastructure and safety for electric vehicle users will be answered.